La gènesi dels somatismes: accions humanes fossilitzades - Sánchez-López, Elena (Studia Romanica Posnaniensia, 2021)
Somatic idioms – those including a part of the body – have been traditionally studied from a synchronic perspective, yielding different explanations for their semantic value. The main objective of this paper is to highlight the diachronic origin of idiomatic meaning, by illustrating the process of phraseologization from a historical, usage-based perspective. As the first step, we will reflect on the general nature of phraseological meaning, and then on the semantic particularities of somatic idioms. Secondly, we will carry out a corpus-based diachronic analysis of the Catalan idiom tapar-se el nas (to hold one’s nose) within the framework of the Invited Inference Theory of Semantic Change. The different stages of the process will be exemplified and discussed. As a result, a new notion of somatic idioms as frozen human actions will be presented.